MANAJEMEN KEPENGAWASAN PROFESIONALISME GURU MASA PANDEMI DI MTS MIFTAHUL FALAH DISKI - Budi Budi; Mulkan Hasibuan; Mesiono Mesiono (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
The management of supervision of teacher professionalism during the COVID-19 pandemic is intended to determine teacher performance so that the supervision and professionalism of teachers during the COVID-19 pandemic can also be measured for the implementation of follow-up to advance learning. This qualitative research is descriptive and makes the researcher the main instrument. The results of the study showed that the supervision plan for teachers during the COVID-19 pandemic was carried out by the supervisory team and the madrasa head integrated into the madrasa annual plan. Organizing resources for the implementation of supervision by dividing tasks to the deputy head of the madrasah and supervisors. Implementation of madrasa supervision plans in the form of online meetings, individual coaching and guidance, and implementation of lesson study activities to improve teacher skills and professionalism.